Tantangan Penerapan Program Kartu Pra Kerja Tahun 2020: Studi Tenaga Kerja Terdampak Covid 19 - Nanda Azizah, Rahma; Damayanti, Keisya; Rizkia Fanita, Andhila; Ikhsan Ananta, Muhammad; Ridwan (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The Indonesian government launched the Pre-Employment Card Program in 2020 to respond to the economic impact of the COVID-19 pandemic. The goal of this policy is to reduce the unemployment rate and revive the national economy by offering financial assistance and skill training to individuals affected by layoffs. To assess the effectiveness of the program in this context from the agenda-setting stage to evaluation it is crucial to use the policy cycle theory. Although this program is intended to reach everyone, accessibility has become a major issue. This is especially true for people living in remote areas who do not have access to digital infrastructure. Although a fully digital approach ensures administrative efficiency, this approach has proven difficult for people who are less familiar with technology. Moreover, the targeting of beneficiaries poses a problem because most beneficiaries are formal workers, not the unemployed, who should be the main focus of the program. Although this program offers valuable lessons about the difficulties in socio-economic policy-making, a thorough analysis of the Prakerja Card policy cycle shows that there is still room for improvement. A strong conceptual framework for evaluating the success of this program is provided by the integration of human resource theory and Maslow's hierarchy of needs.